Peningkatan Literasi Data Melalui Pelatihan Data Science untuk Siswa SMKN 2 Kraksaan - Matlubul Khairi; Muhammad Riski; Moh. Miftahul Rosiqin; Ahmad Roziq Arifin; Moh. Fatoni Ramadani Irsyad; Mardin Mardin (Fakultas Teknik Universitas Cenderawasih, 2024)
The background of this community service focuses on the increasing need for data literacy in the digital age, particularly at SMKN 2 Kraksaan. The school faces challenges in improving students' understanding of data science, which is crucial for preparing them for Industry 4.0. The service aims to enhance students' data literacy through data science training, including understanding basic concepts, data processing techniques, and data analysis. The method involves delivering material, practical sessions using Python programming, and evaluation through pre-tests and post-tests. The training aims to help students understand and apply data science in practical contexts. Evaluation results show that the training is effective in improving students' understanding, with most participants showing significant improvement in their ability to read, process, and analyze data. Although the training facilities are adequate, it is recommended to enhance learning materials and additional resources for future training to ensure even better success.